Cochrane Database of Systematic Reviews 2011
DOI: 10.1002/14651858.cd008274.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of weight-reducing diets in hypertensive patients

Abstract: Long-term effects of weight-reducing diets in hypertensive patients (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 62 publications
1
18
0
1
Order By: Relevance
“…We used a more comprehensive approach of subgrouping studies based on behavioural interventions such diet, exercise and lifestyle changes to better reflect the evidence in the current literature. In addition to a modest reduction observed for measures of adiposity such as weight in kilograms, BMI and waist circumference, our review also found associated reductions in intermediate physiological outcomes such as blood pressure and incidence of type 2 diabetes, which reinforces the findings of other systematic reviews 87,88,89 documenting reduction in the need for pharmacologic therapy for blood pressure and glycemic control as a potential clinical benefit of modest weight loss.…”
Section: Comparison With Other Studiessupporting
confidence: 84%
“…We used a more comprehensive approach of subgrouping studies based on behavioural interventions such diet, exercise and lifestyle changes to better reflect the evidence in the current literature. In addition to a modest reduction observed for measures of adiposity such as weight in kilograms, BMI and waist circumference, our review also found associated reductions in intermediate physiological outcomes such as blood pressure and incidence of type 2 diabetes, which reinforces the findings of other systematic reviews 87,88,89 documenting reduction in the need for pharmacologic therapy for blood pressure and glycemic control as a potential clinical benefit of modest weight loss.…”
Section: Comparison With Other Studiessupporting
confidence: 84%
“…32,33 Similarly, the impact of weight management on hypertension risk in HIV-infected individuals is not well studied, despite evidence that interventions that prevent weight gain are associated with lower blood pressure and reduced use of antihypertensive medications in HIV-uninfected cohorts. [34][35][36] However, research among HIV-uninfected populations combined with our study findings suggests that weight maintenance or planned weight loss could play a crucial role in diabetes and blood pressure control and prevention among HIV-infected black women who present with high obesity prevalence. More work to determine the most effective interventions to achieve this goal is warranted.…”
Section: Obesity Race Sex and Chronic Disease In Hivmentioning
confidence: 67%
“…Weight reduction leads to a decrease in hypertension (Siebenhofer et al, 2011) and diabetes (Lindstrom et al, 2013). In this study, only one sixth of the participants diagnosed with overweight/obesity reported being on a slimming diet.…”
Section: Obesitymentioning
confidence: 54%